ФОРМУВАННЯ У СТУДЕНТІВ ПРИРОДНИЧИХ СПЕЦІАЛЬНОСТЕЙ ПЕДАГОГІЧНИХ ЗАКЛАДІВ ВИЩОЇ ОСВІТИ ЦІЛІСНОГО УЯВЛЕННЯ ПРО ПРИРОДУ - Колесник Марина Олександрівна (International Journal of Innovative Technologies in Social Science, 2020)
The article tackles the issue of construing the educational content from the standpoint of interdisciplinary causative-systemic approach and previously introduced pattern of shaping pedagogical universities' students' universal scientific worldview (USW). The paper discusses theoretical premises of forming future natural sciences' teachers' integral image of Nature. The suggested approach advocates the integration of data from diverse fields of science in the process of modeling educational content, discusses the notion of the "image of the world" and allocates it in the structure of natural- scientific education. Construing respective academic courses' content encompasses the focal idea of natural causality. The article presents the results of the suggested USW model's analysis and dwells on the results of implementing an experimental course into a curriculum. The paper highlights the said model's axiological potential.